Behavioral, Biochemical and Histopathological effects of Standardised Pomegranate extract with Vinpocetine, Propolis or Cocoa in a rat model of Parkinson's disease. Issue 2 (15th March 2022) - Ali, Azza A.; Kamal, Mona M.; Khalil, Mona G.; Ali, Shimaa A.; Elariny, Hemat A.; Bekhit, Amany; Wahid, Ahmed
ABSTRACT: Introduction: Parkinsonism is a neurodegenerative disorder. Pomegranate (POM) has been previously shown to have a dopaminergic neuroprotective effect against parkinsonism. Objective: The aim of the current study is to investigate the possible effect of POM in combination with each of vinpocetine, propolis, or cocoa in the treatment of parkinsonism disease even without being given as adjuvant to L-dopa . Methods: Rats were divided into seven groups, one normal and six RT model groups. One of the RT groups (2.5 mg/kg/48 h/10 doses sc), for 20 days served as non-treated parkinsonism model, whereas the others were treated with either L-dopa (10 mg/kg, p.o./day) or with POM (150 mg/kg, p.o./day) together with each of the following; vinpocetine (VIN) (20 mg/kg, p.o./day), propolis (300 mg/kg, p.o./day), cocoa (24 mg/kg, p.o./day). Motor and cognitive performances were examined using four tests (catalepsy, swimming, Y-maze, open field). Striatal dopamine, norepinephrine, serotonin, GABA, glutamate, acetylcholinesterase, GSK-3β, BDNF levels were assessed as well as MDA, SOD, TAC, IL-1β, TNF-α, iNOs, and caspase-3. Also, histopathological examinations of different brain regions were determined. Results: Treatment with L-dopa alone or with all POM combination groups alleviated the deficits in locomotor activities, cognition, neurotransmitter levels, acetylcholinesterase activity, oxidative stress, and inflammatory markers as well as caspase-3 expression induced by RT. Conclusion: Combinations of POM with each of VIN, propolis, or cocoa have a promising disease-modifying antiparkinsonian therapy even without being given as an adjuvant to L-dopa.